Ganoderma lucidum polysaccharide exerts anti-tumor activity via MAPK pathways in HL-60 acute leukemia cells. (2nd January 2016) - Yang, Guohua; Yang, Lei; Zhuang, Yun; Qian, Xifeng; Shen, Yunfeng
Abstract: In this study, we investigated the anti-tumor activity both in vitro and in vivo of a polysaccharide obtained from Ganoderma lucidum on HL-60 acute myeloid leukemia cells, and focused on its targeting effect on mitogen-activated protein kinase (MAPK) pathways. It was found by the methods such as western blot and flow cytometry (FCM), that G. lucidum polysaccharide (GLP) blocked the extracellular signal-regulated kinase/MAPK signaling pathway, simultaneously activated p38 and JNK MAPK pathways, and therefore regulated their downstream genes and proteins, including p53, c-myc, c-fos, c-jun, Bcl-2, Bax, cleaved caspase-3 and cyclin D1. As a result, cycle arrest and apoptosis of HL-60 cells were induced. Therefore, GLP exerted anti-tumor activity via MAPK pathways in HL-60 acute leukemia cells.